Understanding How Universal Vouchers Have Impacted Urban School Districts’ Enrollment in Chile - Portales, Jaime; Vasquez Heilig, Julian (Education Policy Analysis Archives, 2014)
Findings from this study show that educational and mobility opportunities for families and students participating in the Chilean voucher system are not homogenously distributed. Some families and students use and benefit from the system, while others will remain marginalized. The quantitative results in this study demonstrate that students of relatively higher SES living in mid-high or mid-low poverty districts receive the benefit from vouchers. These students may move from one public school to another, from a public school to private-voucher school in the same area, from one district to another, or from a public school in an area to a private-voucher school in another district. Meanwhile, low-income counterparts living in high-poverty areas are excluded from the system and tend to remain at their public neighborhood school.